Medium to long-term results after reconstruction of bone defects at the knee with tumor endoprostheses - Kinkel, Stefan; Lehner, Burkhard; Kleinhans, Jennifer A.; Jakubowitz, Eike; Ewerbeck, Volker; Heisel, Jens Christian (Journal of surgical oncology, 2010)
Limb salvage and reconstruction with tumor endoprostheses is considered as therapeutic standard in the treatment of bone defects at the knee. Few studies report long-term results so far.